Analysis of Community Satisfaction with Public Services in the Liaison Agency of North Sumatra Province - Situmorang, Frida; Nefianto, Tirton (CV. Publikasi Indonesia, 2025)
The North Sumatra Provincial Liaison Agency plays a strategic role in facilitating communication between the provincial government and the North Sumatran diaspora, particularly those residing in Jakarta. Despite recent improvements in facilities and infrastructure, challenges remain in service delivery—especially in terms of accessibility for people with disabilities and the limited accommodation capacity of the Provincial Government Mess. This study aims to evaluate the quality of public services at the Liaison Agency and identify gaps between community expectations and the services provided. Using a qualitative descriptive method, data were collected through in-depth interviews with key informants and community satisfaction surveys. The findings reveal that although some service standards have been met, there is still a significant disparity between public expectations and actual service performance. Contributing factors include underdeveloped infrastructure, insufficient digitization of services, and limited dissemination of public policies. The research highlights the urgent need for inclusive infrastructure improvements, the adoption of digital-based service models, and enhanced human resource capacity. The implications suggest that by implementing innovative and inclusive public service strategies, the North Sumatra Provincial Liaison Agency can significantly improve citizen satisfaction and strengthen its role as a bridge between the provincial government and the community.